Pathogenic microbes contaminating mobile phones in hospital environment in Northeast India: incidence and antibiotic resistance - Christine Vanlalbiakdiki Sailo; Puja Pandey; Subhajit Mukherjee; Zothan Zami; Ralte Lalremruata; Lalnun Nemi; Nachimuthu Senthil Kumar (Tropical Medicine and Health, 2019)
Abstract Background The present study attempts to identify and determine the pattern of drug susceptibility of the microorganisms present in mobile phones of health care workers (HCWs) and non-HCWs in a hospital environment. Mobile phones of 100 participants including both genders were randomly swabbed from nine different wards/units and the bacterial cultures were characterized using VITEK 2 system. Results Forty-seven mobile phones were culture positive and a total of 57 isolates were obtained which consisted of 28 Gram-positive organisms and 29 Gram-negative organisms. The predominating organisms were Acinetobacter baumannii and Staphylococcus hominis. Among all the isolates from the mobile phones of HCW and non-HCWs, five isolates had ESBL and three isolates had colistin resistance. Incidentally, MRSA was not found on the mobile phones tested. The isolated organisms showed 100% susceptibility to linezolid, daptomycin, vancomycin, imipenem, meropenem, gentamicin, amikacin, ciprofloxacin and tigecycline, while high resistance was shown against benzylpenicillin (75.0%), cefuroxime and cefuroxime axetil (56.5%). Non-HCWs’ mobile phones were more contaminated as compared to HCWs (P = 0.001) and irrespective of individuals’ gender or toilet habits, both Gram-positive and Gram-negative organisms were present on the mobile phones. Conclusion This study reports for the first time that the mobile phones of non-health care workers harbour more bacterial diversity and are more prone to cause transmission of pathogens. This study can serve to educate the public on personal hand hygiene practices and on maintaining clean mobile phones through antiseptic measures.